2001
DOI: 10.1063/1.1405146
|View full text |Cite
|
Sign up to set email alerts
|

Group velocity and propagation losses measurement in a single-line photonic-crystal waveguide on InP membranes

Abstract: Single-line photonic-crystal waveguides are investigated. Photoluminescence experiments and three-dimensional calculation are performed and allow a clear identification of the guided modes. The propagation properties of the latter (group velocity, losses) are extracted from photoluminescence spectra obtained on closed waveguides which act as linear cavities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 22 publications
1
67
0
Order By: Relevance
“…10]. We add the following two remarks: a) the influence of the facet terminations can also play an important role [90], which could allow a systematic investigation of QD coupling as a function of sample length; and b) similar features in the PC waveguide LDOS have been observed experimentally [91].…”
Section: The "Finite-size" Pc Waveguidementioning
confidence: 99%
“…10]. We add the following two remarks: a) the influence of the facet terminations can also play an important role [90], which could allow a systematic investigation of QD coupling as a function of sample length; and b) similar features in the PC waveguide LDOS have been observed experimentally [91].…”
Section: The "Finite-size" Pc Waveguidementioning
confidence: 99%
“…Fringes can be observed using the broad distribution of the QDs. 13 In the linear region of the dispersion relation the fringes are equally spaced and get closer together as the frequency approaches the band edge. Since the cavity resonance was positioned in the region with equidistant fringes, we concluded that the coupling occurs in the linear region ͓Fig.…”
mentioning
confidence: 99%
“…which relates the wavevectors k x of the FP resonances to the fluid-filled cavity length L through an integer p. 18,19 The wavelengths of the experimental dips have been superimposed onto the dispersion curve of the infiltrated waveguide mode of Fig. 2͑d͒, calculated using a threedimensional ͑3D͒ plane-wave method with a supercell approach ͑RSoft's BANDSOLVE͒ using the PCS parameters mentioned earlier.…”
mentioning
confidence: 99%